2009
DOI: 10.1002/rcm.4253
|View full text |Cite
|
Sign up to set email alerts
|

Rapid differentiation of isobaric and positional isomers of structurally related glycosides from Phytolacca bogotensis

Abstract: Through the action of glycosyltransferases, a plant can biosynthetically assemble small different aglycons or 'templates' to various polysaccharides to produce numerous glycoconjugates differing in the type of the attached aglycon, the anomeric configuration of C-1 of the glycosylating sugar, the type of sugar and the different position of attachments of the sugar unit present in the polysaccharide chain. The position of attachments and the anomeric configuration of the different sugar present in the polysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Five GOTCAB saponins (A-E), previously isolated from Gypsophila trichotoma roots, were used as references. Saponins were characterized on the basis of extensive NMR analysis ( 1 H, 13 C NMR, COSY, HSQC, HMBC, TOCSY, HSQC-TOCSY, ROESY), completed by HR-ESI-MS and ESI-MS n analyses [9]. The structures of the saponin references are given in Fig.…”
Section: Gotcab Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Five GOTCAB saponins (A-E), previously isolated from Gypsophila trichotoma roots, were used as references. Saponins were characterized on the basis of extensive NMR analysis ( 1 H, 13 C NMR, COSY, HSQC, HMBC, TOCSY, HSQC-TOCSY, ROESY), completed by HR-ESI-MS and ESI-MS n analyses [9]. The structures of the saponin references are given in Fig.…”
Section: Gotcab Referencesmentioning
confidence: 99%
“…An aliquot of the crude extract (1 g) was fractionated by a low pressure liquid chromatography over a C18 column (310 × 25 mm,40-63 µm) (Merck, Germany) using a binary gradient of methanolwater (10:90 -100:0) to afford 20 fractions (each 25 ml). Fractions (10)(11)(12)(13) were separated by repeated semi-preparative HPLC on Kinetex C18 (150 x 10 mm, 5 µm) (Phenomenex, USA) and gave 18 fractions (each 5ml). Semi-preparative HPLC was performed on a chromatographic system Varian equipped with a ternary pump Model 9012, a Rheodyne injector with 200 µL loop and an UV/VIS detector Model 9050 set at 210 nm.…”
Section: Isolation and Nmr Analysis Of A Compound 1 From G Glomeratamentioning
confidence: 99%
See 1 more Smart Citation
“…By using the previously described approach [14], a total of twenty-five saponins were identified in a polar complex mixture from Ectyoplasia ferox , from which ulososides A and D, and urabosides A and B are well-known molecules (Figure 1 and Table 1). None of the other twenty-one identified compounds have been previously reported for this species.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches to metabolite identification that use MS n fragmentation often require manual intervention by mass spectrometry experts. [9,[15][16][17] Recently, more automated approaches are reported that greatly facilitate this tedious analysis. [14,[18][19][20][21] Some of the methods focus on predicting fragmentation patterns in silico.…”
mentioning
confidence: 99%